Dichlorocarbenation of polar olefins in conditions of microwave irradiation - Yu. G. Borisova; A. I. Musin; R. M. Sultanova; S. S. Zlotskii (Тонкие химические технологии)
Objectives. To evaluate the influence and efficiency of using microwave irradiation on the dichlorocarbenation of polar olefins. To determine the conditions (reaction time and process temperature) under which the maximum yield of target gem-dichlorocyclopropanes is achieved.Methods. The target compounds were obtained by classical methods of organic synthesis— acetalization of polyols and dichlorocarbenation of unsaturated compounds. The preparation of gem-dichlorocyclopropanes was carried out using the microwave activation method on a Sineo device (microwave system for organic synthesis, made in China). In order to determine the qualitative and quantitative composition of the reaction masses, gas–liquid chromatography (using the Kristall 2000 hardware complex), mass-spectroscopy (using Chromatek-Kristall 5000M device with NIST 2012), and nuclear magnetic resonance spectroscopy (using Bruker AM-500 device with operating frequencies of 500 and 125 MHz) were carried out.Results. Under microwave irradiation at 25°C for 2 h with the maximum yield (92–98%), the target substituted gem-dichlorocyclopropanes were obtained: 2-(2,2-dichloro-3-methylcyclopropyl)-1,3-dioxolane, 2-(2, 2-dichloro-3-phenylcyclopropyl)-1,3-dioxolane, 8,8-dichloro4-isopropyl-3,5-dioxabicyclooctane, diethyl-2,2-dichloro-3-phenylcyclopropane-1,1-dicarboxylate, and diethyl-2,2-dichloro-3isopropylcyclopropane-1,1-dicarboxylate.Conclusions. Under the conditions herein proposed, the use of the microwave stimulation method in the dichlorocarbenation of double C=C bonds containing polar substituents allows the reduce the temperature and reaction time to be significantly reduced, and the yield of target gem-dichlorocyclopropanes to be increased.